2016
DOI: 10.1210/jc.2015-4066
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Morphogenetic Protein 15 Up-Regulates the Anti-Müllerian Hormone Receptor Expression in Granulosa Cells

Abstract: Altogether, these results suggest that the mechanisms of action of BMP15 on AMHR2 and AMH expression are different, and that by stimulating AMHR2 and AMH expression in GCs BMP15 enhances AMH inhibitory actions in GCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 41 publications
1
32
1
2
Order By: Relevance
“…It has been previously demonstrated that GDF9 slightly enhances the stimulatory effect of BMP15 alone on AMH expression in ovine GCs obtained from preantral follicles (Pierre et al 2016). In contrast, we observed a strong synergism between GDF9 and BMP15 on the expression of AMH in humans, whereas either factor has negligible effects on AMH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been previously demonstrated that GDF9 slightly enhances the stimulatory effect of BMP15 alone on AMH expression in ovine GCs obtained from preantral follicles (Pierre et al 2016). In contrast, we observed a strong synergism between GDF9 and BMP15 on the expression of AMH in humans, whereas either factor has negligible effects on AMH.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is also possible that the receptors used by the heterodimers are not expressed in ovine GCs or that the heterodimers are more active in human than in ovine GCs. An example of this possibility is that in ovine GCs, Pierre et al (Pierre et al 2016) could show an increase in AMH promoter activity after treatment with GDF9 and BMP15. In contrast, we were not able to do so, suggesting species-specific differences.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the pathogenesis of ovarian cysts must consider many potential contributing factors (Fitko et al, 1995(Fitko et al, , 1996Kozłowska et al, 2013;Pierre et al, 2016). As such, it is not yet possible to exclude contributions by BMP-15 and GDF-9 during cyst formation Błaszczyk, 2014, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A 2,252 (–2,199/+53)-bp human AMHR2 promoter (Ref-SeqGene NG-015981) [31, 40] was prepared by cloning successively a 428 (–375/+53)-bp fragment and a 1,825-bp distal promoter fragment (–2,199/–374) into the Bgl II and Hin dIII sites of the pGL2-basic vector. The short construct contains only the 428-bp fragment (428-h AMHR2 -Luc).…”
Section: Methodsmentioning
confidence: 99%
“…FSH and estradiol were reported to downregulate Amhr2 transcripts in rat ovarian follicles [37], and an inhibitory effect of LH and estradiol on AMHR2 mRNA levels was reported in human luteinized granulosa cells [38, 39]. Contrasting with gonadotropins, bone morphogenetic protein 4 (BMP4) and BMP15 were recently demonstrated to upregulate AMHR2 mRNA levels in human granulosa cells through transcriptional activation of the AMHR2 promoter [40]. However, the signaling pathways and mechanisms by which these hormones regulate the transcriptional activity of the AMHR2 gene are still unknown.…”
Section: Introductionmentioning
confidence: 99%